FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEBIASAAN MEROKOK PADA REMAJA LAKI – LAKI DI KECAMATAN TANJUNG REJO PERCUT SEI TUAN - Panjaitan, Masriati; Purba, Agnes; Kasinem, Kasinem (JURNAL HEALTH REPRODUCTIVE, 2017)
Adolescent male smoking is an incredibly familiar, smoking can give pleasure for the smoker but on the other hand may adversely affect the smoker themselves and the poeple around him. According to the World Health Organization in 2011 in Indonesia there are 67 % of adolescentmale smoke and according to the 2012 Demographic and Health Survey Adolescent Reproductive Health are the precentage of smoking at the age of 15 – 19 years in males was 74,4 %. The purpose of this study is to determine factors related to smoking behavior in adolescent men in Medan City Regional High School Years 2015. This study uses a quantitative approach with a cross – sectional study design. The population in this study are all high school students School ( SMAN) in the city of Medan as many as 14431 poeple with a total sample of 400 sample. Collecting data using primary and secondary data. Data processing is done by a process of editing, coding and tabulating. Analysis of data using univariate, bivariate andmultivariate analyzes. The result showed there is a relationship attitudes about smoking with smoking behavior in adolescents ( p value 0,002), there is a relationship forming identity with smoking behavior in adolescent ( p value 0,000), there is a connection allowance with smokingbehavior in adolescents ( p value 0,000), there is a relationship cigarette advertising with smoking behavior in adolescent ( p value 0,007), there is a relationship price cigarette with smoking behavior in adolescent ( p value 0,000), there is a relationship support older poeple with smoking behavior in adolescent ( p value 0,018), there was a relationship peer support with smoking behavior in adolescent ( p value 0,000), the factors knowledge no significant a relationship with smoking behavior in adolescent ( p value 0,283) and the factors support the family members no significant a relationship smoking behavior in adolescent ( p value 1,000), and No smoking area no significant a relationship with smoking behavior in adolescent ( p value 0,200). The dominant variable related to smoking behavior in adolescent is peer support variable ( p = 0,000 ; OR 4,220 ) it means to support peer support has a value of 4 has the habit of smoking compared with peer support doesnot support. There for, to adolescent in order to follow the group - a group that increase the skills of decision making for health independently and follow self – help groups and to help promote the campaign – anti – smoking compaigns in schools and the surrounding environment